1981
DOI: 10.1159/000272654
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Creative Abilities and Self-Esteem across the Adult Life-Span

Abstract: The purpose of this study was to explore the relationship between divergent thinking and self-esteem in age groups across the adult life-span. A total of 218 subjects ranging in age from 18 to 84 years responded to a personal data inventory, a self-esteem measure, and a taped auditory free-response exercise in divergent thinking. Scores were obtained for fluency, flexibility, and originality of thought, and for self-esteem. Self-esteem significantly predicts divergent thinking across age groups; age does not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…In the literature on creativity and age three previous empirical studies [Bromley, 1956;Alpaugh and Birren, 1977;Jaquish and Ripple, 1981] concluded that there were de clines in creative productivity and creative thinking with age. However, none of these studies included information concerning the history of creative activity of their subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature on creativity and age three previous empirical studies [Bromley, 1956;Alpaugh and Birren, 1977;Jaquish and Ripple, 1981] concluded that there were de clines in creative productivity and creative thinking with age. However, none of these studies included information concerning the history of creative activity of their subjects.…”
Section: Discussionmentioning
confidence: 99%
“…They also sug gested that the age differences in preference for complexity and divergent thinking ex plained a decline in creative production with increasing age. Jaquish and Ripple [1981] investigated the relationships between three scales of the Guilford Tests of divergent thinking, fluency, flexibility, and originality, and self-esteem among a sample of 218 men and women aged 18-84 years. They found that the oldest age group (61-84 years) was less fluent and less flexible than the younger age groups, but scored as well as the youngest age group (18-25 years) on the originality scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jaquish and Ripple (1981) found that adults report somewhat lower self-esteem in late adulthood (age 61-81 years) than in middle adulthood (age 40 -60 years). Tiggemann and Lynch (2001) found that women age 70 -85 years had slightly lower self-esteem than women in their 60s.…”
Section: Old Agementioning
confidence: 92%
“…Generally, these studies show small, gradual increases in global self-esteem (Gove et al, 1989;Helson & Wink, 1992;Jaquish & Ripple, 1981;Lall, Jain, & Johnson, 1996;R. E. Roberts & Bengtson, 1996).…”
Section: Adulthoodmentioning
confidence: 98%